The Use of E-portfolio Assessment To Improve Students' Writing Ability (RETAIN, 2020)
Writing has been known as one of the product skill in learning English. According to Brown (2007), writing is not only about how the students put the words in a paper, but also composing the idea in order to persuade, inform, and entertain the readers. Therefore, the teachers need to provide the proper method to involve and guide the students in the process of writing. Hence, the combining of the technology to the assessment through the process is needed. Therefore, this study focused on the use of e-portfolio assessment in improving students writing ability. This study used quasi-experimental research which has 68 students of tenth graders as the participants. The participants were decided into two groups; experimental group and control group. The instruments of the study were pre-test and post-test in order to know the significant improvement in students’ writing ability after using e-portfolio as the assessment. Then, the study was analyzed using a Wilcoxon signed-rank test and Mann Whitney U in SPSS 24th edition since the data was skewed. Turning to the result of this study, it presented that both groups had improved scores on the post-test after the treatment. However, the experimental group had statistically higher scores than the control group. Another that, the comparison of the students’ post-test showed that there were statistically significant differences between the two groups. In other words, the use of e-portfolio, which combines technology as a tool in the process of teaching-learning, can help the students in improving their writing skill.